2007
DOI: 10.1890/06-2038.1
|View full text |Cite
|
Sign up to set email alerts
|

Escape From Uv Threats in Zooplankton: A Cocktail of Behavior and Protective Pigmentation

Abstract: In order to avoid environmental threats, organisms may respond by altering behavior or phenotype. Using experiments performed in high-latitude Siberia and in temperate Sweden, we show for the first time that, among freshwater crustacean zooplankton, the defense against threats from ultraviolet radiation (UV) is a system where phenotypic plasticity and behavioral escape mechanisms function as complementary traits. Freshwater copepods relied mainly on accumulating protective pigments when exposed to UV radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
158
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(163 citation statements)
references
References 51 publications
(72 reference statements)
3
158
0
Order By: Relevance
“…Cladocerans have several efficient mechanisms to avoid UVR (Hansson et al., 2007; Rautio & Tartarotti, 2010). Here, we have demonstrated that their ability to exhibit different traits to counteract UVR damage is not only species‐specific, but also differs between lineages within the same species but with different evolutionary histories, and that the involved trade‐offs depend on the environment in which the organisms live.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cladocerans have several efficient mechanisms to avoid UVR (Hansson et al., 2007; Rautio & Tartarotti, 2010). Here, we have demonstrated that their ability to exhibit different traits to counteract UVR damage is not only species‐specific, but also differs between lineages within the same species but with different evolutionary histories, and that the involved trade‐offs depend on the environment in which the organisms live.…”
Section: Discussionmentioning
confidence: 99%
“…UVR treatment was applied by covering the experimental flasks with a UVR‐transparent acrylic sheet (UV‐transmitting PLEXIGLAS ® GS; Röhm GS 2458; Darmstadt, Germany) that has an average transmittance of 85% between 300 and 400 nm, while the Non‐UVR treatment was achieved through a UVR‐screening acrylic sheet (UV‐absorbing PLEXIGLAS ® GS; Röhm GS 233; Darmstadt, Germany) that cuts 100% radiation below 370 nm. For a full spectral transmittance of plexiglasses see Hansson, Hylander, and Sommaruga (2007). For both treatments, ultraviolet radiation at an intensity of 135 μW cm 2 was provided by three UVR fluorescent lamps (UVA‐340; Q‐panel) with a maximum emission in the UV‐A band (340 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Elsewhere, daphnids also appear to be more responsive than slower-growing copepods to warming (Strecker et al 2004) despite their inability to track spring algal blooms that occur earlier under warmer spring conditions (Winder and Schindler 2004). D. catawba has been shown to better tolerate the combined effect of warming and exposure to ultraviolet radiation owing to enhanced photoenzymatic repair (Hansson et al 2007;Williamson et al 2007). In addition, D. catawba is considered a very effective competitor under severe food limitation (Tessier 1986), possibly benefiting from the small cryptophytes that were most abundant under the warm droughtlike conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Most other pontellid genera are considered either oceanic or neritic and also neustonic (Silas and Pillai 1973;Conley and Turner 1985). The genus Labidocera Lubbock, 1853, has large eye lenses for scanning (Land 1988), and their morphology is adapted for sea surface dwelling, as they are highly pigmented (Herring 1965), an adaptation to reduce the effects of damaging ultraviolet radiation and to hide from surface predators (Hansson et al 2007;Hunt et al 2010;Mojib et al 2014). The pigment specific to pontellid copepods is a blue carotenoprotein (Zagalsky and Herring 1972), and they are able to adjust their level of pigmentation depending on risks in their immediate environment (Hansson 2000).…”
Section: Introductionmentioning
confidence: 99%